Analisis Risiko Pada Proses Rigging dan Lifting Menggunakan Metode HIRARC di Production Platform Module Erection Area PT. McDermott Indonesia - Nasywwa Khoirunnisa; Alrido Martha Devano; Syiffa Rahmania (Politeknik Negeri Batam, 2025)
PT. McDermott Indonesia is a company engaged in offshore construction services. Workplace accidents in the offshore construction industry are often due to poor weather conditions, inadequate work locations, equipment failures, and incompetent employees. This study aims to determine the risk level in the rigging and lifting process using the HIRARC method as an effort to achieve zero accidents in the Production Platform Module Erection Area. This research uses a descriptive qualitative approach. The research subjects consist of 5 informants: a rigging superintendent, an HSE specialist, a rigger, a crane operator, and a mechanic foreman, assisted by interview guidelines and a risk matrix. The study results indicate 21 potential hazards across 4 work stages and 10 work processes, categorized into 6 low risk, 8 medium risk, 13 high risk, and 4 extreme risk. Risk control is carried out by HSE procedures and the lifting plan, and it is recommended to use PPE consistently. In conclusion, the risk analysis in the rigging and lifting process has been conducted according to procedures, but updates to the TRA are necessary to reduce increasing risks. It is recommended to enhance employee awareness and discipline regarding the importance of implementing HSE measures.